Creative pasts : historical memory and identity in western India, 1700-1960 - Deshpande, Prachi (Cultures of history, 2007)
"The "Maratha period" of the seventeenth and eighteenth centuries, when an independent Maratha state successfully resisted the Mughals, is a defining era in the history of the region of Maharashtra in western India. In this book, Prachi Deshpande considers the importance of this period for a variety of political projects including anticolonial/Hindu nationalism and the non-Brahman movement, as well as popular debates throughout the nineteenth and twentieth centuries concerning the meaning of tradition, culture, and the experience of colonialism and modernity." "Creative Pasts examines the practices of historiography and popular memory within a particular colonial context, and illuminates the impact of colonialism on colonized societies and cultures. Furthermore, it shows how modern history and historical memory are jointly created through the interplay of cultural activities, power structures, and political rhetoric."--BOOK JACKET.